(e, 2e) simple ionization of H3+ by fast electron impact: use of triangular three-center continuum and bound state wave functions. (14th June 2017) - Obeid, S; Chuluunbaatar, O; Joulakian, B B
Abstract: The variation of the multiply differential cross section of the (e, 2e) simple ionization of H 3 +, with the incident and ejection energy values, as well as the directions of the ejected and scattered electrons, is studied. The calculations have been performed in the frame of the perturbative first Born procedure, which has required the development of equilateral triangular three center bound and continuum state wave functions. The results explore the optimal conditions and the particularities of the triangular targets, such as the appearance of interference patterns in the variation of the four fold differential cross section (FDCS) with the scattering angle for a fixed orientation of the molecule. The comparison between the results obtained by two H3 + ground wave functions, with and without a correlation term r 12, shows that the effect of correlation on the magnitude of the triple differential cross section is not large, but it produces some modification in the structure of the FDCS.